Emergence of Huntington Disease in a Man With a Premorbid Criminal Lifestyle - Hedlund, Jonatan; Masterman, Thomas (Frontiers in Psychiatry, 2019)
We present here a case in which Huntington disease (HD) was diagnosed upon forensic-psychiatric evaluation of a 34-year-old male repeat offender. Despite a family history of HD, as well as overt delusions and motor pathology, the disease had not been recognized at an earlier stage, and the patient was serving a prison sentence at the time of diagnosis. The case highlights difficulties court officials may face with regard to identifying severe psychiatric and neurological disorders in repeat offenders. Such offenders’ gradually deteriorating status could be overlooked by the court, even in cases in which a tailored judicial process is warranted. Also, the present case highlights the risk of using antipsychotic medication to treat HD, since it may worsen sufferers’ capacity to recognize emotions in others, thereby increasing the risk of altercations and criminal activity.